Anti-atherosclerotic effect of incretin mimetics: a meta-analysis of randomized controlled trials. Issue 6 (2nd November 2018) - Barbarawi, Mahmoud; Aburahma, Ahmed; Zayed, Yazan; Osman, Mohammed; Rashdan, Laith; Swaid, Bakr; Bachuwa, Ghassan
ABSTRACT: Background : Diabetes is a very common cause of cardiovascular disease, and metformin remains the first-line treatment of diabetes. Many trials were conducted to prove the efficacy and safety of other antidiabetic medication as the best add-on medication. Objectives: We aimed to evaluate the atherosclerotic effect of incretin mimetics in patients with diabetes.Methods : We searched in PubMed, clinicaltrials.gov and Cochrane Library for randomized controlled trials (RCTs) comparing incretin mimetic with conventional treatment. The primary outcome was the change in carotid intima-media thickness (CIMT) at the end of the trials.Results : Five RCTs (n = 1241), the mean age of patients included in the trials is 64.3 ± 11.4. The primary outcome was statistically significant for CIMT improvement in terms of long-term follow-up analysis between the incretin mimetic group and conventional group (mean difference [MD] −0.031; 95% Confidence interval [CI] −0.049 to 0.012; P = 0.001), whereas at short-term follow-up it wasn't (MD −0.004; 95% CI −0.024 to 0.016; P = 0.7) in the overall group of study participants. Additionally, the mean change in body mass index (BMI) (MD 0.064; 95% CI −0.54 to 0.67; P = 0.8), and mean change in systolic blood pressure (MD −0.42; 95% CI −3.2 to 2.3; P = 0.8) or diastolic blood pressure (MD 0.25; 95% CI −1.18 to 1.68; P = 0.7) were not significant.Conclusion : Long-term use of incretin mimetic medication results in significant improvement of atherosclerosis, which leads to fewer vascular events, with no apparent effect on blood pressure or BMI. Further dedicated trials are required to show the superiority of adding these medications to conventional treatment versus placebo.